CONCENTRATION CATALYSTS: VISUAL APPROACHES FOR EFFECTIVE ELLT - B, Karunakaran; A, Noble Jebakumar (ShodhGyan-NU: Journal of Literature and Culture Studies, 2024)
The research titled "Concentration Catalysts: Visual Approaches for Effective ELLT" delves into the influence of visual aids on concentration in English Language Learning and Teaching (ELLT). Through a study involving 50 undergraduate students, the effectiveness of diverse visual aids was explored. Results revealed that integrating visual images, animations, and image comparisons significantly heightened students' concentration during ELLT sessions. The study introduced a website tailored to student interests, incorporating a variety of visual aids, leading to increased engagement and improved concentration. The findings underscore the importance of incorporating visual materials and interactive resources in ELLT, catering to diverse learning styles. Educators and instructional designers are encouraged to embrace the potential of visual aids to create an enriched learning environment, ultimately fostering heightened concentration and improved learning outcomes in ELLT.